2008
DOI: 10.1159/000145384
|View full text |Cite
|
Sign up to set email alerts
|

Axillary Web Syndrome after Sentinel Node Biopsy

Abstract: Background: Axillary web syndrome (AWS) is a self-limiting cause of morbidity in the early postoperative period after axillary surgery, but it is encountered also after sentinel lymph node biopsy. The syndrome is characterized by cords of subcutaneous tissue extending from the axilla into the medial arm. Case Report: Here, we report a patient presenting with AWS several weeks after sentinel lymph node biopsy. Conclusion: AWS has been reported to be resolved spontaneously in all patients 8–16 weeks after axilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
4

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 7 publications
0
11
0
4
Order By: Relevance
“…We summated the subcategories into “paresthesia” and a “decreased ROM of the ipsilateral shoulder” for the purposes of comparison across the trials and our study. To date, while only the technical outcomes are available from NSABP B-32 [33-34] and no more than a 3-year follow-up of morbidity [35-36], our report provides clinically important information not only with regard to the outcomes but also the rates of complications at 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…We summated the subcategories into “paresthesia” and a “decreased ROM of the ipsilateral shoulder” for the purposes of comparison across the trials and our study. To date, while only the technical outcomes are available from NSABP B-32 [33-34] and no more than a 3-year follow-up of morbidity [35-36], our report provides clinically important information not only with regard to the outcomes but also the rates of complications at 10 years.…”
Section: Discussionmentioning
confidence: 99%
“…Menezes et al [12] observed that 85.7% of patients with limited range of motion have AWS, and Moskovitz et al [13] verified that 74% of the patients who showed AWS had joint restriction. These divergent results in the literature could be because of the different methodological designs because most articles about AWS are case reports [6,7,10,[14][15][16][17] or retrospectives studies [12,13,18] where the identification of AWS may have induced the symptoms. In this study, all women were subjected at palpation and examination of the affected arm independent of the symptoms reported.…”
Section: Discussionmentioning
confidence: 99%
“…Because this syndrome can develop after a patient's last surgical follow-up visit [22], it is important that family physicians, as well as oncologists and surgeons, be able to clinically diagnose the syndrome so that they can reassure their patients that the condition is usually self-limiting [29] and make referrals to a physical therapist if the patient's range-of-motion is especially compromised or if she is experiencing pain during everyday activities.…”
Section: Resultsmentioning
confidence: 99%